2011
DOI: 10.1016/j.juro.2010.12.094
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism of the ORAI1 Gene is Associated With the Risk and Recurrence of Calcium Nephrolithiasis

Abstract: To our knowledge this is the first study identifying the novel polymorphisms of the ORAI1 gene, which may predispose to the risk of calcium nephrolithiasis and disease recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…A single missense mutation in ORAI1 was found in patients with severe combined immune deficiency syndrome. In 2011, genetic polymorphisms of ORAI1 were reported to associate with the risk and recurrence of calcium nephrolithiasis (130) and HLA-B27-positive AS (131). In the KD study, no significant association between OARI1 genotypes ORAI1 and KD clinical parameters (such as CAL formation or IVIG treatment responses) was found.…”
Section: Genetic Polymorphisms Of the Itpkc Signaling Pathway In Kawamentioning
confidence: 98%
“…A single missense mutation in ORAI1 was found in patients with severe combined immune deficiency syndrome. In 2011, genetic polymorphisms of ORAI1 were reported to associate with the risk and recurrence of calcium nephrolithiasis (130) and HLA-B27-positive AS (131). In the KD study, no significant association between OARI1 genotypes ORAI1 and KD clinical parameters (such as CAL formation or IVIG treatment responses) was found.…”
Section: Genetic Polymorphisms Of the Itpkc Signaling Pathway In Kawamentioning
confidence: 98%
“…The localized phenotype found restricted to certain tissues contrast to the ubiquitous expression of Orai1 or STIM1, suggesting compensation mechanisms in the unaffected tissues, presumably by their homologues Orai2, Orai3 and STIM2 [ 176,243,244 ] . In human, other studies found strong correlation between presence of certain single nucleotide polymorphisms (rs12313273) in Orai1 alleles and risk or recurrence of stone generation in kidney, referred to as calcium nephrolithiasis [ 247 ] . Diseases associated to absence of Orai2, Orai3 or STIM2 function have not been identifi ed in human yet.…”
Section: Soce and Diseasementioning
confidence: 99%
“…Furthermore, this mutation in ORAI1 has been shown to cause dysfunctions in Ca 2+ release-activated Ca 2+ (CRAC) channels and impairs the immune system [67] . In 2011, a genetic polymorphism of ORAI1 was reported to be associated with the risk and recurrence of calcium nephrolithiasis [68] . In the study of Kawasaki disease, no significant association between genotype and allele frequency of the five Table 2.…”
Section: Genetic Polymorphisms Of the Itpkc Signaling Pathway In Patimentioning
confidence: 99%